Taxonomic review of the Rhagonycha flava species group (Coleoptera, Cantharidae), with descriptions of fourteen new species from China - Xiao, Yun-Feng; Liu, Hao-Yu; Yang, Xing-Ke; Yang, Yu-Xia (Zootaxa, 2024)
The species of Rhagonycha Eschscholtz, 1830 with yellowish elytra from the Oriental Region are reviewed and defined as Rh. flava species group. Fourteen new species are described, including Rh. nigricolor sp. nov. and Rh. trimacula sp. nov. (China, Sichuan), Rh. falcata sp. nov., Rh. tibetanimima sp. nov., Rh. similis sp. nov., Rh. maculaticeps sp. nov., Rh. curtiapicis sp. nov., Rh. acutiapicis sp. nov., Rh. ocula sp. nov. and Rh. weixiensis sp. nov. (China, Yunnan), Rh. longicornis sp. nov. and Rh. zayuensis sp. nov. (China, Xizang), Rh. flavimima sp. nov. (China, Hubei), and Rh. guizhouensis sp. nov. (China, Guizhou). The new species are illustrated, and figures of their habitus, aedeagi, abdominal sternites VIII and internal genitalia of females are provided. Ten previously known species are supplementarily described, and illustrations of their habitus and female reproductive systems are provided for the first time: Rh. albolimbata Pic, 1926, Rh. bimucronata Švihla, 2005, Rh. flava (Pic, 1926), Rh. furcatiformis Wittmer, 1997, Rh. hubeiana Wittmer, 1997, Rh. limbatella Wittmer, 1997, Rh. spinosa Wittmer, 1997, Rh. tibetana Švihla, 2002, Rh. weichowensis Wittmer, 1997, and Rh. yunnana Wittmer, 1997. Besides, the habitus photos of the following species are provided with for the first time: Rh. furcata Wittmer, 1997, Rh. testaceopallipa Wittmer, 1997, Rh. tryznai Švihla, 2002, Rh. albidipennis Pic, 1923, Rh. bomdiensis Wittmer, 1989, Rh. disconigra (Pic, 1907), Rh. manipurensis Wittmer, 1989 and Rh. meghalayana Wittmer, 1989. Additionally, distribution maps are presented for the similar species either in the appearances or aedeagi. Now the Rh. flava species group includes a total of 39 species, for which an identification key and a checklist of the Rh. flava species group are provided, respectively.